Prediction of Optimal Daily Step Count Achievement from Segmented School Physical Activity - Ryan D. Burns; Timothy A. Brusseau; James C. Hannon (Advances in Public Health)
Optimizing physical activity in childhood is needed for prevention of disease and for healthy social and psychological development. There is limited research examining how segmented school physical activity patterns relate to a child achieving optimal physical activity levels. The purpose of this study was to examine the predictive relationship between step counts during specific school segments and achieving optimal school (6,000 steps/day) and daily (12,000 steps/day) step counts in children. Participants included 1,714 school-aged children (mean age = 9.7±1.0 years) recruited across six elementary schools. Physical activity was monitored for one week using pedometers. Generalized linear mixed effects models were used to determine the adjusted odds ratios (ORs) of achieving both school and daily step count standards for every 1,000 steps taken during each school segment. The school segment that related in strongest way to a student achieving 6,000 steps during school hours was afternoon recess (OR = 40.03; P<0.001) and for achieving 12,000 steps for the entire day was lunch recess (OR = 5.03; P<0.001). School segments including lunch and afternoon recess play an important role for optimizing daily physical activity in children.